Percolations and phase transitions in a class of random spin systems - Daletskii, A. (Methods of Functional Analysis and Topology, 2015)
The aim of this paper is to give a review of recent results of Yu. Kondratiev, Yu. Kozitsky, T. Pasurek and myself on the multiplicity of Gibbs states (phase transitions) in infinite spin systems on random configurations, and provide a `pedestrian’ route following Georgii–Haggstrom approach to (closely related to phase transitions) percolation problems for a class of random point processes.